Effect of transfer from a pediatric to adult cystic fibrosis center on clinical status and hospital attendance. Issue 7 (18th April 2021) - Collins, Rachel; Singh, Bhajan; Payne, Donald N.; Bharat, Chrianna; Noffsinger, William; Dhaliwal, Satvinder S.; O'Dea, Christopher; Mulrennan, Siobhain
Abstract: Aim: Transfer from pediatric to adult services could lead to clinical deterioration, few studies have examined this. We sought to examine the clinical impact of a structured individualized transition and transfer process in patients with cystic fibrosis (CF). Methods: Medical records of all patients with CF in Western Australia who transferred from a pediatric center (Princess Margaret Hospital for Children) to an adult CF center (Sir Charles Gairdner Hospital) between 2008 and 2012 were reviewed. Data were extracted for 2 years before and after transfer. The number of CF outpatient visits, inpatient days, and home intravenous antibiotic therapy (HIVT) days were recorded at yearly intervals before and after transfer. Sputum culture results at transfer were collected. All respiratory function and anthropometric data over the 4 years were extracted. Results: Forty‐two patients with CF were transferred between 2008 and 2012. The mean age at transfer was 18.9 years (range 17–22). Compared to 1‐year pre‐transfer, the frequency of outpatient visits at 1‐ and 2‐year post‐transfer increased. After transfer, there was no change in BMI, HIVT days, or inpatient days, and no acceleration in the expected decline in FEV1. Conclusion: This study found that transfer from a pediatric to an adult CF center using a structured, individualized transition and transfer process was not associated with accelerated clinical deterioration.